Strengthening religious values and student discipline through Ma'had Darunnajah programs - Salsabillah, Aulia; Andini, Febi; Aulia, Febriyanti; Naura, Rizky; Maya, Viona; Pamungkas, Bayuaji Arya (PT. Pena Produktif Kreatif, 2025)
Ma'had Darunnajah is an Islamic educational institution that strives to instill religious values and discipline in both the learning environment and students' daily lives. This study aims to explore the strategies used by Ma'had Darunnajah to implement religious culture and discipline through its various activities. These activities include religious programs and efforts to cultivate disciplined character among students. Using a qualitative approach with a phenomenological method, the research collected data through in-depth interviews with four Ma'had mentors and student representatives, both male and female. The findings reveal that Ma'had activities play a significant role in shaping students’ character, particularly in terms of religious commitment and discipline. Furthermore, students who were more actively involved in Ma'had responsibilities tended to achieve higher academic performance compared to their less active peers. These insights are expected to serve as a reference model for other educational institutions seeking to enhance character development and academic achievement through similar Ma'had-based programs.